(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this research is to determine the difficulties faced by selected senior high school g12 honor students of Bestlink College of the Philippines in terms of Academic Performance, Educational Competency, and Cognitive Behavior. The results of this study reveal that the Blended Learning difficulties faced by our respondents are well outperformed by them as they become more resilient: academic performance shows that they are all cooperative and open to collaboration, and using their gadgets is useful to form schoolwork and also they often share their knowledge through recitations. Educational Competency shows that they are a good communicator as a student; creativity and resourcefulness are some of the skills seen in them while using straight English is often performed. Cognitive Behavior shows that studying is stressful yet beneficial to use it as a foundation to overcome difficulties. This study recommended encouraging students to focus on the solution, not the problem itself. Inspire students to believe that this difficulty will end soon. Also, setting a goal is a must. Furthermore, using the skills and competencies to promote changes, critical thinking BCPians not only flow in the mind but also in our actions or will. Applying and sharing the innovative effects of Blended Learning will make our School resilient.